Burden and severity of children's hospitalizations by respiratory syncytial virus in Portugal, 2015–2018. Issue 1 (14th November 2022) - Bandeira, Teresa; Carmo, Mafalda; Lopes, Hugo; Gomes, Catarina; Martins, Margarida; Guzman, Carlos; Bangert, Mathieu; Rodrigues, Fernanda; Januário, Gustavo; Tomé, Teresa; Azevedo, Inês
Abstract: Background: Respiratory syncytial virus (RSV) is a leading cause of acute lower respiratory infection (ALRI) in young children and is of considerable burden on healthcare systems. Our study aimed to evaluate ALRI hospitalizations related to RSV in children in Portugal. Methods: We reviewed hospitalizations potentially related to RSV in children aged <5 years from 2015 to 2018, using anonymized administrative data covering all public hospital discharges in mainland Portugal. Three case definitions were considered: (a) RSV‐specific, (b) (a) plus unspecified acute bronchiolitis (RSV‐specific & Bronchiolitis), and (c) (b) plus unspecified ALRI (RSV‐specific & ALRI). Results: A total of 9697 RSV‐specific hospitalizations were identified from 2015 to 2018—increasing to 26 062 for RSV‐specific & ALRI hospitalizations—of which 74.7% were during seasons 2015/2016–2017/2018 (November–March). Mean hospitalization rates per season were, for RSV‐specific, RSV‐specific & Bronchiolitis, and RSV‐specific & ALRI, respectively, 5.6, 9.4, and 11.8 per 1000 children aged <5 years and 13.4, 22.5, and 25.9 in children aged <2 years. Most RSV‐specific hospitalizations occurred in healthy children (94.9%) and in children aged <2 years (96.3%). Annual direct costs of €2.4 million were estimated for RSV‐specific hospitalizations—rising to €5.1 million for RSV‐specific & ALRI—mostly driven by healthy children (87.6%). Conclusion: RSV is accountable for a substantial number of hospitalizations in children, especially during their first year of life. Hospitalizations are mainly driven by healthy children. The variability of the potential RSV burden across case definitions highlights the need for a universal RSV surveillance system to guide prevention strategies.